Sport Specialization’s Impact on Youth Athletes’ Intention of Quitting Sports and Reasons Why Athletes Quit Sports Stratified by Sex and Race or Ethnicity - Kevin M. Biese; Abigail Godejohn; Christopher Stratton; Lace Luedke (Sports Health: A Multidisciplinary Approach, 2026)
Background: This study examined (1) the association of sport specialization with the intention of youth athletes quitting sports, and (2) the association of sex with reasons for quitting, while exploring reasons for quitting sports by varying racial and ethnic groups. Hypothesis: Sport specialization will increase the intention of wanting to quit sports and female athletes will report more social reasons for quitting sport compared with male athletes. Study Design: Cross-sectional. Level of Evidence: Level 3. Methods: Online anonymous surveys were distributed via social media. The survey included the Wisconsin Sport Specialization Questionnaire (WISSQ), questions about the intention to quit any or all sports, reasons for quitting, and demographic information. The WISSQ contained 3 scored domains (physical/social/motivational) that were aggregated to an overall score (0-100). Participants rated their intention of quitting sports in the next year on a 5-point Likert scale (“extremely unlikely” to “extremely likely”). Ordinal regressions were used to assess the association of the intention of quitting sport with WISSQ domain and overall scores. Chi-square analyses assessed the association of reasons for quitting with sex (male/female). Results: The study included 266 participants (male, 119 [58%]; White, 139 [68%]; age, 15.3 ± 1.5 years; WISSQ overall score, 48.7 ± 16.1; physical domain, 57.2 ± 27.8; motivational domain, 54.5 ± 23.8; social domain, 48.7 ± 16.1). Most participants answered that they were “extremely” or “somewhat unlikely” to quit any or all sports next year (160 of 266; 60%). The WISSQ motivational domain score showed a significant association with the intention of quitting sport (odds ratio = 0.98; 95% CI, 0.96-0.99). Female athletes selected coaching (male, 11 of 119 (9%); female, 18 of 86 (21%); P = 0.02) and competition (male, 3 of 119 (3%); female, 9 of 86 (11%); P = 0.02) more frequently as reasons for quitting compared with male athletes. Conclusion: The motivation to specialize in sport may improve sport retention for the following year. Clinical Relevance: The motivation to specialize must be balanced with potential negative effects of sport specialization. Further understanding of how coaches and competition negatively impact female youth athletes’ experiences is paramount.